2021
DOI: 10.3390/s21196527
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Material Search for Infrared Markers under Non-Heating and Heating Conditions

Abstract: Research on optimal markers for infrared imaging and differences in their characteristics in the presence of heat sources has not yet been performed. This study investigates optimal material combinations for developing an accurate and detachable infrared marker for multiple conditions in the medium wave infrared (MWIR) region. Based on four requirements, 11 material combinations are systematically evaluated. Consequently, the optimal marker differs in relation to the presence of specular reflection components.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The test results demonstrated that the thermal insulation property of Ion/Clay‐F is comparable to cotton fabric at temperatures below 70 °C, potentially due to the heat reflection from liquid metal. [ 72 ]…”
Section: Resultsmentioning
confidence: 99%
“…The test results demonstrated that the thermal insulation property of Ion/Clay‐F is comparable to cotton fabric at temperatures below 70 °C, potentially due to the heat reflection from liquid metal. [ 72 ]…”
Section: Resultsmentioning
confidence: 99%